Botswana : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper and Statistical Appendix provides medium-term estimates of the cost of the government's current anti-HTV/AIDS policies and programs in Botswana. The paper throws light on the policy challenges that Botswana authorities face in combating the crisis. The findings suggest that the cost of treating HIV/AIDS patients is likely to be high, about 10 percent of GDP, by 2010 (using the baseline estimates). The paper also analyzes Botswana's approach to medium-term fiscal management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet